Cotidiano e trabalho: trabalhadores ceramistas em Monte Carmelo/MG 1970/2000 - Silva, Patrícia Rodrigues da (2001)
This dissertation is an interpretation about the ways of life of ceramic workers in the city of Monte Carmelo / MG seeking to understand the meanings they give to their lives. Thus, starting from an analysis that sought to understand the role and interpretation of workers, from the development and consolidation of the military industry in Monte Carmelo in the 1970s to the latest technological transformations many industries went through in the late 1990s. I sought to understand the daily struggle of these workers both at work and outside, highlighting the forms of resistance (outside the union and collective political action) and their moments of accommodation in the face of the strong exploitation to which their workforce is subjected.